2020
DOI: 10.7150/thno.41802
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes-mediated Transfer of miR-125a/b in Cell-to-cell Communication: A Novel Mechanism of Genetic Exchange in the Intestinal Microenvironment

Abstract: Glucagon-like peptide-2 (GLP-2), a key factor in intestinal rehabilitation therapy of short bowel syndrome (SBS), may require cell-to-cell communication to exert its biological functions. However, understanding of the mechanism remains elusive. Here, we report participation of exosomal miR-125a/b in GLP-2 mediated intestinal epithelial cells-myofibroblasts cross-talk in intestinal microenvironment. Methods: The effects of GLP-2 on the proliferation and apoptosis of intestinal epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Then the miRNAs silence gene expression by inducing mRNA degradation or translation inhibition ( Garcia et al, 2020 ). Exosomal miR-125a/b inhibits intestinal epithelial cell proliferation and promotes cell apoptosis by suppressing myeloid cell leukemia-1 ( Cheng et al, 2020 ). Our previous study has demonstrated that milk-derived exosomal miR-219 and miR-4334 reduce LPS-induced inflammation in intestinal epithelial cells through the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Then the miRNAs silence gene expression by inducing mRNA degradation or translation inhibition ( Garcia et al, 2020 ). Exosomal miR-125a/b inhibits intestinal epithelial cell proliferation and promotes cell apoptosis by suppressing myeloid cell leukemia-1 ( Cheng et al, 2020 ). Our previous study has demonstrated that milk-derived exosomal miR-219 and miR-4334 reduce LPS-induced inflammation in intestinal epithelial cells through the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we used high-throughput ITS sequencing to comprehensively analyze intestinal fungal dysbiosis in type 2 SBS rats. Our previous study found that GLP-2 could promote intestinal mucosal proliferation [ 1 ]. However, whether GLP-2 could ameliorate the intestinal microbiota dysbiosis of SBS has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 short bowel syndrome model was created with SD rats (male, 8 weeks old, 250–260 g; Charles River, Beijing, China), according to a previously reported method [ 1 ]. Rats were kept at a temperature of 21 °C to 25 °C, humidity of 52 to 62%, and a 12/12-h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations